2010
DOI: 10.1371/journal.pcbi.1000873
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Gene Regulatory Networks by Fluctuating Selection and Intrinsic Constraints

Abstract: Various characteristics of complex gene regulatory networks (GRNs) have been discovered during the last decade, e.g., redundancy, exponential indegree distributions, scale-free outdegree distributions, mutational robustness, and evolvability. Although progress has been made in this field, it is not well understood whether these characteristics are the direct products of selection or those of other evolutionary forces such as mutational biases and biophysical constraints. To elucidate the causal factors that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 94 publications
4
30
0
Order By: Relevance
“…For instance, properties such as robustness, modularity, redundancy, complexity, and evolvability can be measured by pathway connectivity and have been argued to convey adaptive value to the individual [4,16-18]. A recent study invoked fluctuating phenotypic selection to explain the evolution of scale-free distributions and pathway complexity [19]. However, whether adaptation can operate uniformly on the genome scale to have consistent effect on regulatory complexity is an open debate [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, properties such as robustness, modularity, redundancy, complexity, and evolvability can be measured by pathway connectivity and have been argued to convey adaptive value to the individual [4,16-18]. A recent study invoked fluctuating phenotypic selection to explain the evolution of scale-free distributions and pathway complexity [19]. However, whether adaptation can operate uniformly on the genome scale to have consistent effect on regulatory complexity is an open debate [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that when subjecting CRNs to the various neutral evolutionary forces and tracing their trajectory in time, many of these topological patterns may simply arise spontaneously due to the forces of mutation, recombination, gene duplication, and genetic drift (10, 12). These studies call into question arguments that were made in favor of adaptive explanations for the emergence and conservation of CRN properties (8,(13)(14)(15) and identify important parameters that may significantly affect the evolution of CRNs from a neutral perspective. Specifically (12), they highlighted the role that promoter length, binding-site size, and population size may play in forming certain topological patterns known as motifs.…”
mentioning
confidence: 99%
“…In particular, an important insight into improving the quantifiability of neutral trends is that promoter length and the spontaneous gain and loss rates of TF binding sites (TFBS) vary substantially within a genome and that reducing each distribution to one value potentially eclipses important emergent properties and structure at the network level. Previous work assumed all promoters were the same length (10,12,15,16), whereas the current work incorporates variability in promoter lengths. Finally, by subjecting a population of individuals whose genotypes are thus constructed to nonadaptive forces of evolution, we provide a simulation framework for generating data corresponding to a null model of only neutral forces.…”
mentioning
confidence: 99%
“…Iwasaki, Tsuda, and Kawata developed an individual-based approach to the GRN modeling [37, 38]. The GRN of each individual had both phenotypic and regulatory genes, each gene was composed of a cis-regulatory region and a coding region, and a cis-regulatory region was composed of cis-sites for specific transcription factors.…”
Section: Evolutionary Physiology and Biochemistry -Advances And Perspmentioning
confidence: 99%
“…In contrast, simple GRNs have mutational robustness only because of their small mutational target size. Iwasaki and co-authors found that the level of CGVs in a population was mainly determined by the order (weighted size) of GRNs and concluded that the outgrowth of GRNs and adaptation to new environments are mutually facilitating, resulting in sustainable evolvability [37]. …”
mentioning
confidence: 99%